CABI agriculture and bioscience - C.A.B. International (BioMed Central, 2020)
"CABI Agriculture and Bioscience is a broad-scope, open access journal publishing original research and data in all fields related to agriculture and the biosciences. This includes traditional themes such as plant science and plant breeding, horticulture, forestry, plant pathology, entomology and pest management, livestock and animal science, invasive species, environmental and soil science, and social sciences. The journal encourages inter- and cross-disciplinary research that connects these 'vertical' subject areas through 'horizontal' themes, including: genomics; big data; climate change; evidence-based agriculture; technology; sustainability, restoration and conservation; agro-ecology; food security and nutrition; and modelling."--Publisher
Keywords: Agriculture : Periodicals; Life sciences : Periodicals; Agriculture; Life sciences